Thinking and deciding - Baron, Jonathan, 1944- (Cambridge : Cambridge University Press, 2008)
Beginning with its first edition and through subsequent editions, Thinking and Deciding has established itself as the required text and important reference work for students and scholars of human cognition and rationality. In this fourth edition, first published in 2007, Jonathan Baron retains the comprehensive attention to the key questions addressed in the previous editions - how should we think? What, if anything, keeps us from thinking that way? How can we improve our thinking and decision making? - and his expanded treatment of topics such as risk, utilitarianism, Baye's theorem, and moral thinking. With the student in mind, the fourth edition emphasises the development of an understanding of the fundamental concepts in judgement and decision making. This book is essential reading for students and scholars in judgement and decision making and related fields, including psychology, economics, law, medicine, and business.
Part I. Thinking in general : What is thinking? : Types of thinking ; The search-inference framework ; Thinking about beliefs ; How do search processes work? ; Knowledge, thinking, and understanding -- The study of thinking : Descriptive, normative, and prescriptive ; Methods for empirical research ; Development of normative models ; Descriptive models and heuristics ; Development of prescriptive models ; Classification of biases -- Rationality : Good thinking and goal achievement ; Rationality and emotion ; Rationality and belief ; Are people ever really irrational? -- Logic : What is logic? ; Types of logic ; Difficulties in logical reasoning ; Mental models ; Logical errors in hypothesis testing ; Extensions of logic -- Part II. Probability and belief : Normative theory of probability : What is probability? Constructing probability judgments ; Well-justified probability judgments ; Evaluating probability judgments ; Bayes's theorem -- Descriptive theory of probability judgment : Accuracy of probability judgments ; Heuristics and biases in probability -- Hypothesis testing : Hypotheses in science ; The psychology of hypothesis testing -- Judgment of correlation and contingency : Correlation, cause, contingency ; Accuracy of judgment ; Attentional bias ; Effects of prior belief -- Actively open-minded thinking : Examples of actively open-minded thinking ; Myside bias and irrational belief persistence ; Effect of active open-mindedness on outcomes ; Determinants and related phenomena ; Factors that moderate belief persistence -- Part III. Decisions and plans : Normative theory of choice under uncertainty : Expected-utility theory ; Why expected-utility theory is normative ; The utility of money -- Descriptive theory of choice under uncertainty : Experienced, predicted, and decision utility ; Bias in decisions under uncertainty ; Prospect theory ; Rank-dependent utility theories ; Emotional effects of outcomes ; The ambiguity effect ; Uncertainty and reasons for c
Title from publisher's bibliographic system (viewed on 18 Jul 2016).
Keywords: elektronické knihy; electronic books; Thought and thinking; Decision making